Documentation of Tuberculosis Statistic Data Reporting at Primary Healthcare Facilities in Malang City - Prisusanti, Retno Dewi; Afifah, Lilik (Procedia of Engineering and Life Science, 2024)
Background: Tuberculosis is one of the top ten causes of death in the world, and is a serious public health problem in Indonesia. Malang City is one of the regions in Indonesia with a high incidence of TB. Based on data from the Malang City Health Office in 2023, there are 2,500 new TB cases with a death rate of 200 people. This shows that TB is still a public health problem that needs serious attention in Malang City. Objective: what is to be achieved in this study in order to find out the implementation and process of documenting the reporting of tuberculosis statistical data at the first level health service facility in the city of Malang. Research method: the research method uses qualitative descriptive with one respondent in each Health Service Facility that has been interviewed directly. Results: The results of this study refer to the implementation and process of documenting the reporting of tuberculosis statistical data at the first level of service facilities in Malang City. Conclusion: Documentation of TB statistical data reporting at FKTP Malang City is still not optimal. Efforts need to be made to improve the documentation of TB statistical data reporting at the Malang City FKTP.